The creative citizen: citizenship building in urban areas - Carvalho, Cláudia Pato (2011)
The current work explores the significance of citizenship in the contemporary world, suggesting a new approach to its realization, where artistic practice and the development of cultural awareness combine to produce the creative citizen. This research uses case studies from three Boston metropolitan area neighbourhoods in Massachusetts, USA, to reflect on arts and culture as platforms to re-address citizenship at the community level. The case studies address examples where citizenship is explored through the development of inter-ethnic and face-to-face connections as platforms of artistic inclusion, the creation of a local identity associated with an Arts District, and through physical space appropriation and reinforcement of cultural identity. The relationship between urban public space, community, and culture is understood as a platform that may offer new strategies for urban space revivification, and specific strategies of civic engagement and leadership in these communities, providing impetus for the development of creative citizens.